Influence of Internet of Things and Work Life Balance on Employee Job Satisfaction - Liu Zhijian (Dinasti Publisher, 2024)
Within the field of human resource management research, the article The Influence of the Internet of Things and Work Life Balance on Employee Job Satisfaction is a review of scholarly literature. The goal of this article's authoring is to develop a hypothesis about the relationship between variables that can be applied to future management science and human resources management research projects. The descriptive qualitative research methodology is applied. Relevant data from earlier studies was gathered for this study and sourced from scholarly web resources like Google Scholar, Sinta journal, publish or perish, and digital reference books. The findings of this study are as follows: 1) Work life balance affected employee job satisfaction; and 2) Internet of things affected employee job satisfaction